Interplay of NK cells and monocytes in vascular inflammation and myocardial infarction - Knorr, Maike; Münzel, Thomas; Wenzel, Philip (Frontiers in Physiology, 2014)
Inflammatory monocytes and macrophages have been identified as key players in the pathogenesis of atherosclerosis, arterial hypertension and myocardial infarction. They become powerful mediators of vascular inflammation through their capacity to secrete and induce the production of proinflammatory cytokines, chemokines and adhesion molecules and through the production of reactive oxygen species mainly via their NADPH oxidase. Importantly, a crosstalk exists between NK cells and monocytes that works via a feedforwad amplification loop of T-bet/Interferon-gamma/interleukin-12 signalling, that causes mutual activation of both NK cells and monocytes and that fosters recruitment of inflammatory cells to sites of inflammation. Recently, we have discovered that this crosstalk is crucial for the unrestricted development of angiotensin II induced vascular injury in arterial hypertension, the most important risk factor for atherosclerosis and cardiovascular disease worldwide. In this review, we will also discuss possible implications of this interplay between NK cells and monocytes for the pathogenesis of coronary atherosclerosis and myocardial infarction and potential therapeutic options.